Detailed estimation method of heat generation during charge/discharge in lithium‐ion battery using equivalent circuit. Issue 12 (4th December 2019) - Inui, Yoshitaka; Hirayama, Satoshi; Tanaka, Tadashi
Abstract: Lithium‐ion batteries are becoming practically used for high power applications such as electric vehicles. For this purpose, some estimation technique of battery heat generation is inevitable. The authors, therefore, have already proposed a simple estimation method of the heat generation in lithium‐ion batteries during their charge/discharge using internal equivalent resistance and confirmed validity of the method for constant current discharge patterns. The merit of this method is its simplicity but it has already been made clear that its versatility for various current patterns is not enough. Considering these facts, in this study, the authors newly proposed a detailed estimation method of the heat generation in lithium‐ion batteries during their charge/discharge using equivalent circuit. The authors compared the estimation results of the heat generation in lithium‐ion battery for various constant or pulse current charge/discharge patterns through the newly proposed detailed estimation method with the estimation results through the conventional simple estimation method and measured results through a calorimeter for the corresponding current patterns. The versatility of the newly proposed detailed estimation method was successfully confirmed through these comparisons, indicating the validity and necessity of the proposed method.